Swarm intelligence. Volume 1, - Tan, Ying, 1964- (IET control, robotics and sensors series, 2018)
The book focuses on the principle and the current approaches of swarm intelligence algorithms for presenting the latest achievements in the principle and typical algorithms in recent years. The book mainly introduces the basic principles of typical swarm intelligence algorithms and some of their efficient improvements. Specifically, it not only includes the introductions and improvements of typical PSO, ACO and typical swarm intelligence algorithm as well as swarm robotics methods; furthermore, it also includes parts of the general swarm intelligent method research until now.